Electoral Cycles in MPs' Salaries: Evidence from the German States - Björn Kauder; Manuela Krause; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2016)
Members of parliament (MPs) often decide on their own salaries. Voters dislike self-serving politicians, and politicians are keen to gratify their voters. In line with the political business cycle theories, politicians thus may well delay deciding on increases in salaries until after elections. We investigate electoral cycles in the salary increases of German state MPs. Using data for 15 states over the period 1980-2014, the results do not show that decisions on increases in MPs' salaries were influenced by elections. In fact, MPs' salaries increased by 0.30 to 0.37 percent when employees' salaries increased by one percent. Politicians can increase their salaries at any point of time in the legislative period: understanding that all politicians benefit from an increase in salaries, voters may only be disenchanted with politics in general, without punishing individual incumbent parties.
Keywords: D72; H70; A13; 330; electoral cycles; political business cycles; election-motivated politicians; MPs' salaries; rent extraction